2020
DOI: 10.1021/acsapm.0c00911
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Study of Polytetrafluoroethylene Defluorination for Tribocharging Applications

Abstract: Polytetrafluoroetyhlene (PTFE) is one of the most efficient polymers for green energy-harvesting devices like triboelectric nanogenerators because of its high capability of acquiring and retaining negative charge. Despite its extensive use, the relation between PTFE triboelectric behavior and its electronic properties has never been analyzed. To shed light on this important feature we have studied the electronic properties of PTFE low-index surfaces in the high pressure phase by means of density functional the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…A single PTFE chain was chosen to minimize the configurational complexity, as we showed in a previous study that interchain interactions do not affect PTFE electronic structure. [ 39 ] We found an Au(111) work function value of 5.15 eV, consistent with previous calculations performed [ 44,45 ] and in reasonable agreement with the experimental value of 5.35 eV. [ 46 ] First, we deposited the PTFE chain on gold and studied its more energetically favorable configurations.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…A single PTFE chain was chosen to minimize the configurational complexity, as we showed in a previous study that interchain interactions do not affect PTFE electronic structure. [ 39 ] We found an Au(111) work function value of 5.15 eV, consistent with previous calculations performed [ 44,45 ] and in reasonable agreement with the experimental value of 5.35 eV. [ 46 ] First, we deposited the PTFE chain on gold and studied its more energetically favorable configurations.…”
Section: Resultssupporting
confidence: 89%
“…In a previous study, we have shown that the large PTFE triboelectricity can only occur when it undergoes defluorination, due to its electronic structure. [ 39,40 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a significant amount of research is being devoted to the study of Tribo-Electric Nano-Generators (TENGs) , to optimize their design and predict their performance. This has contributed to an increase in the use of DFT to study triboelectrification. …”
Section: Introductionmentioning
confidence: 99%
“…Based on our first-principles analysis for mechanisms, only interface potential barrier (IV) showed strong correlation with experimentally measured charge density and material-pair dependency; none of the other models successfully account for experimental observations. The detailed analysis for mechanisms (I–III) is presented in SI Note 5 and Figure S4. The interface barrier ( W ) is defined as the difference between the maximum electrostatic potential of the interface and the Fermi level at equilibrium. Figure a schematically illustrates a planar electrostatic potential at contact (i.e., equilibrium), reflecting the change of the average potential along the axis perpendicular to the contact surface ( z -axis).…”
mentioning
confidence: 99%